Triboelectric charge generation by semiconducting SnO2 film grown by atomic layer deposition - Lee, No Ho; Yoon, Seong Yu; Kim, Dong Ha; Kim, Seong Keun; Choi, Byung Joon (KOREAN INST METALS MATERIALS, 2017)
Improving the energy harvesting efficiency of triboelectric generators (TEGs) requires exploring new types of materials that can be used, and understanding their properties. In this study, we have investigated semiconducting SnO2 thin films as friction layers in TEGs, which has not been explored thus far. Thin films of SnO2 with various thicknesses were grown by atomic layer deposition on Si substrates. Either polymer or glass was used as counter friction layers. Vertical contact/separation mode was utilized to evaluate the TEG efficiency. The results indicate that an increase in the SnO2 film thickness from 5 to 25 nm enhances the triboelectric output voltage of the TEG. Insertion of a 400-nm-thick Pt sub-layer between the SnO2 film and Si substrate further increased the output voltage up to similar to 120 V in a 2 cm x 2 cm contact area, while the enhancement was cancelled out by inserting a 10-nm-thick insulating Al2O3 film between SnO2 and Pt films. These results indicate that n-type semiconducting SnO2 films can provide triboelectric charge to counter-friction layers in TEGs.
Keywords: THIN-FILMS; NANOGENERATORS; ENERGY; OXYGEN